PERAN HUKUM INVESTASI DALAM PEMBANGUNAN INFRASTRUKTUR PENDIDIKAN SEKOLAH DASAR DI ACEH UTARA - Nicolo de’Albertgati Mansu G; Fitra Akbar; Audry Salsabila Pasaribu; I Ketut Astawa; Clara Bunga Larasati; Diana Sari (Jurnal Hukum Lex Generalis, 2024)
This research aims to analyze the role of investment law in public infrastructure development with a focus on equitable development in the regions, especially in the education sector in North Aceh. Equitable infrastructure development is one of the main goals of national development policy, but in reality in several regions, such as North Aceh, there is inequality in access to adequate educational infrastructure. This study seeks to explore the extent to which investment legal regulations can play a role in encouraging equitable development, and why, in the case of educational infrastructure development in North Aceh, this has not been achieved. Using a normative juridical approach and empirical studies, this research examines several aspects, including regulations related to investment, the legal framework governing infrastructure development, as well as the influence of the delegation of authority from the central government to regional governments, including in the local economic sector, on the implementation of development policies. This study also highlights the important role of government, both central and regional, in ensuring that investment policies and infrastructure development are carried out in a transparent and accountable manner. Strengthening regulations and increasing supervision are needed to ensure that development can proceed evenly, without intervention from interested parties.